The first biallelic missense mutation in the FXN gene in a consanguineous Turkish family with Charcot-Marie-Tooth-like phenotype - Candayan, Ayşe; Yunisova, Gulshan; Çakar, Arman; Durmuş, Hacer; Başak, A. Nazlı; Parman, Yeşim; Battaloğlu, Esra (Neurogenetics, 2020)
Charcot-Marie-Tooth (CMT) disease is the most common inherited neuropathy with a prevalence of 1 in 2500 individuals worldwide. Here, we report three Turkish siblings from consanguineous parents presenting with a CMT-like phenotype who carry a homozygous c.493C>T, p.Arg165Cys mutation in the FXN gene that is the only known causative gene for Friedreich’s ataxia (FRDA). The identified missense mutation has been reported previously in two FRDA cases in compound heterozygosity with the common GAA repeat expansion in the first intron of the FXN gene. Analysis of skin biopsy samples from our family indicated that the mutation does not affect the expression levels of the frataxin, pointing to functional impairment of the corresponding protein. The CMT phenotype in the siblings was associated with visual impairment, optic nerve atrophy, and dysarthria. To the best of our knowledge, this family represents the first FXN missense mutation in homozygosity and challenges the notion that missense mutations have not been reported yet due to their embryonic lethality. Furthermore, this finding poses an interesting genetic overlap between autosomal recessive CMT and FRDA that we believe may have important implications on understanding the pathogenesis of these neurological disorders.